PERSPECTIVES OF THE METHODS DEVELOPMENT FOR AIRCRAFT MAINTAINABILITY CERTIFICATION - Yu. A. Yaloza; A. N. Petrov (Научный вестник МГТУ ГА)
The paper outlines the main problems and perspectives of methods development for regulation and finding compliance of aircraft during the type design maintainability certification. Mentioned requirements and methods relevance are related to the fact that aircraft continuing airworthiness at the operational stage is possible only with a reasonable combination of the maintenance documentation instructions for continuing airworthiness of a type design and the required level of its maintainability, which both meet the minimum requirements of airworthiness standards. Deficiencies in those requirements and means of compliance have notable influence on the safety and effectiveness of air transportation. Main ICAO standards and international practice of regulation and evaluation of aircraft maintainability and instructions for continuing airworthiness are briefly analyzed. On the base of aircraft maintenance requirements analysis recommendations proposed aimed to further develop regulations and means of compliance for a type design maintainability certification. For solving this problem there is a need to implement certain scientific and practical developments in the domain of integrated logistic support as a technology which integrates the reliability, maintainability and other technical operating capabilities activities for a newly-designed aircraft in order to create its effective maintenance system.  The kinds of requirements within the aviation regulations and means of compliance for them are recommended, which have to be corrected and developed, as well as directions of works necessary for that, including implementation of computer modelling and prototypes testing for showing compliance of aircraft with the maintainability certification requirements. It is shown a need for implementation of the scientific and practical results of research in integrated logistic support domain which allow for interconnect of the reliability and maintainability activities within a new aircraft design in order to integrate systematically reliability requirements with the necessary maintenance action in support of reliability and with the required for those maintenance works level of type design maintainability.